FORECASTING THE NUMBER OF AUDITORS FOR THE SPECIALIZED DENTAL CENTER IN BABYLON USING TIME SERIES (World Economics and Finance Bulletin, 2022)
The Specialized Dental Center in Babylon is considered one of the important centers in the urban time, and the rate of auditors for this center is remarkably high, and annual plans must be drawn up by those concerned to accommodate these numbers. This study aimed to develop standard models to predict the number of auditors expected to arrive at the specialized center to use the Box Jenkins methodology
Keywords: these; Dental; Babylon; concerned